Mastering HDR in Photoshop CS5 - Kloskowski, Matt (Kelbytraining.com, 2010)
"HDR is one of the hottest trends in digital photography. And now Photoshop CS5 has an entirely new set of features aimed at getting you great HDR photos right out of Photoshop (with no 3rd party plug-ins). In this course, HDR Pro Matt Kloskowski shows you how to put those new features to work to create some killer HDR photos"--Resource description page.